Stratigraphic context, geochemical, and isotopic properties of magmatism in the Siluro-Devonian inliers of northern Maine: implications for the Acadian Orogeny - Schoonmaker, A.; Kidd, W.S.; Reusch, D.N.; Dorais, M.J.; Gregg, T.; Spencer, Christopher (American Journal of Science, 2011)
This paper reports detailed stratigraphic analysis, whole rock geochemistry and Nd isotopic ratios of basalts from the northern Maine inliers. These data place constraints on first-order controversies about the tectonic conditions leading up to and during the early stages of the Acadian Orogeny in northern Maine. Late Silurian and early Devonian stratigraphic sequences indicate a progressive change from shallow water and subaerial exposure (Ripogenus and The Forks formations, East Branch Group) to a rapidly subsiding basin prior to the onset of Acadian deformation. Subsidence was accompanied by mafic to intermediate volcanism of the West Branch, Spider Lake, and Fish Pond volcanics, and that continued with intrusion of the syn-deformational Greenville Plutonic Belt, including the Flagstaff Lake Igneous Complex, whose properties we report in this paper. Trace element geochemistry indicates that magmatism is transdiscriminant, showing aspects of within-plate, volcanic arc, and back-arc affinities and Nd isotopic ratios are moderately positive (+2.3 to +3.8) indicating either an uncontaminated and moderately enriched mantle source, or a depleted mantle source contaminated by continental crust. Four possible tectonic models of the Acadian Orogeny and the Siluro-Devonian sedimentary-volcanic sequences of northern Maine are evaluated in the context of a subsiding basin associated with this magmatism developed on the amalgamated Laurentian plate. These include 1) slab detachment during southeast-directed subduction of the Laurentian continental margin; 2) “Laramide-style” thrust basins above a shallow, northwest-dipping subduction zone; 3) back-arc extension followed by thin-skinned shortening above a northwest-dipping subduction zone; and 4) “Moluccan-style” dual-dipping subduction zones.